Narrativas: um olhar sobre o exercício historiográfico na Educação Matemática - Cury, Fernando Guedes; Souza, Luzia Aparecida de; Silva, Heloisa da [UNESP] (UNESP - Universidade Estadual Paulista, Pró-Reitoria de PesquisaPrograma de Pós-Graduação em Educação Matemática, 2014)
This paper presents some of the discussions that has marked the investigative practice of the Group “Oral History and Mathematics Education” (GHOEM). For these researchers the oral history is faced like a qualitative research methodology, whose main focus is the construction of narratives from interview situations. This paper discusses some perspectives related to the use of (narrative) analysis of narratives in/for the History of Mathematics Education.

Este artigo apresenta algumas das discussões que tem marcado a prática investigativa do grupo “História Oral e Educação Matemática” (GHOEM). A História Oral se apresenta como uma metodologia de pesquisa qualitativa cujo foco principal é a construção de narrativas a partir de situações de entrevista. Este texto discute algumas perspectivas vinculadas ao uso de análise (narrativa) de narrativas na/para a História da Educação Matemática.
Narratives: a look at the historiographical exercise in Mathematics Education
Keywords: Educação Matemática; História Oral; Narrativas; Mathematics Education; Oral History; Narratives